2018
DOI: 10.1371/journal.pone.0204377
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of neutrophil to lymphocyte ratio in patients with acute exacerbation of chronic obstructive pulmonary disease

Abstract: ObjectiveThis study aimed to determine the predictive value of the neutrophil to lymphocyte ratio (NLR) in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD).MethodsA retrospective study was conducted from March 2012 to May 2016 in Fuxing Hospital, Capital University of Medical Science. We collected 906 cases (525 males, 381 females, mean age 81.86±9.75 years) diagnosed with AECOPD. The NLR was calculated from their white blood cell (WBC), neutrophil (NEU), and lymphocyte (LYM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 29 publications
0
42
0
1
Order By: Relevance
“…Although lymphocytes play a critical role in the pathogenesis of COPD involving airway and parenchymal inflammation, patients with COPD have also shown a decreased in lymphocyte counts 8 11 . Low lymphocyte count is one of the markers of stress response and the low ratio of lymphocyte in the peripheral blood have the potential to indicate the pathological condition of chronic inflammation 8 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Although lymphocytes play a critical role in the pathogenesis of COPD involving airway and parenchymal inflammation, patients with COPD have also shown a decreased in lymphocyte counts 8 11 . Low lymphocyte count is one of the markers of stress response and the low ratio of lymphocyte in the peripheral blood have the potential to indicate the pathological condition of chronic inflammation 8 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Rapid and proper recognition of these patients along with appropriate treatment may be the only action that prevents respiratory failure and mortality [11][12][13]. Currently, there is no consensus for the assessment of the severity and progression of acute COPD exacerbations by using a clinical tool [5]. Heart failure is also a critical clinical condition with findings such as dyspnoea, orthopnoea, lower limb swelling, and pulmonary congestion because of possible structural and/or functional cardiac abnor-mality with important physiological abnormalities including reduced cardiac output and/or elevated intracardiac pressures [14].…”
Section: Discussionmentioning
confidence: 99%
“…NLR has been used in patients with acute COPD exacerbation in several studies, mostly as an indicator of exacerbation. Teng et al [5] examined the predictive value of NLR in patients with acute COPD exacerbation. Their findings showed that NLR was higher in patients during admission and decreased after treatment according to clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fei et al [18] investigated the role of NLR in the prediction of acute exacerba-A. H. Abdinur, Y. D. Gao Open Journal of Respiratory Diseases tion in COPD patients.…”
mentioning
confidence: 99%